Investigation of the Third-Order Nonlinear Optical Susceptibilities and Nonlinear Refractive Index In Pbs/Cdse/Cds Spherical Quantum Dot - Fatemeh Rahmani; Javad Hasanzadeh (Journal of Optoelectronical Nanostructures, 2018)
In this study the third order nonlinear susceptibilities are theoreticallycalculated for an electron confined in an isolated PbS/ CdSe/ CdS spherical core-shellshellquantum dots. Our calculation is associated with intersubband transitions in theconduction band. We used the effective mass approximation in this study which is asimple and straightforward study of the third-order optical nonlinearity in nanometersizedparabolic quantum dots and solved a three-dimensional Schrӧdinger equation. The thirdorder nonlinear susceptibilities are analyzed as function of core, shell radii. Our studyshow great dependence of third order nonlinear susceptibilities on size of core and shell.Also In the case of Kerr-type nonlinearities, nonlinear refractive index n2 and thenonlinear absorption coefficient β are investigated as function of the ratio k0/n0 (where n0and k0 are the real and imaginary part of linear refractive index respectively) for differentvalue of imaginary and real parts of the third order susceptibility.